KARAKTERISTIK EKOLOGI DAN SOSIAL EKONOMI LANSKAP HUTAN PADA DAS KRITIS DAN TIDAK KRITIS: STUDI KASUS DI DAS BATURUSA DAN DAS CIDANAU - Mimi Salminah; Iis Alviya; Virni Budi Arifanti; Retno Maryani (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
Forests play a vital role in both environmental and economic development. They maintain not only ecological sustainability, but also provide economic resources such as wood and non wood products. To create its sustainability, the forest management must be conducted on the basic of landscape characteristics of the forest itself. This research aims to analyze characteristics of ecology and social economics of the forest landscape in a critical and a non critical watershesds. Understanding of the characteristics is crucial to set a policy for a sustainable forest landscape management system. The Baturusa and the Cidanau watersheds were chosen as research locations based on representation of the critical and the non critical watershed areas. The data from 2009 were analyzed by the GIS and the qualitative descriptive methods. The result showed that ecological characteristics of the Cidanau watershed were better than those of the Baturusa watershed. However, the economic characteristics of the Baturusa watershed were better than those of the Cidanau watershed. In addition, both areas have similar condition in social characteristics. The programs that have positive impacts on the forest landscape characteristics are a payment environmental service mechanism and intensive campaign to the community regarding the importance of forest conservation.